ANALISA DAMPAK FINANCIAL TECHNOLOGY (FINTECH) TERHADAP KEBUTUHAN KAUM MILENIAL - Dian Permata Sari; Nuur Wahid Abdul Majid; Rizki Hikmawan; Hudzaifi Syah Tsalits Taufiqi (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
The rise of online loan advertisements and the ease of accessing and processing loans certainly make them attractive for today's smartphone users. If an offer is given to a customer or client, of course, there is an agreed agreement, so this agreement has various impacts on online loan users. The research method used is qualitative research, using the Likert scale. The use of a sample size of 104 respondents refers to Gay and Diehl's sample size theory in Anwar Sanusi (2012) which states that the minimum number of samples that must be taken is 30 samples. It is hoped that the results of this research will have an impact on the needs, causes, and factors of millennials making online loans on the University in Purwakarta campus.